Microalgae and Phototrophic Purple Bacteria for Nutrient Recovery From Agri-Industrial Effluents: Influences on Plant Growth, Rhizosphere Bacteria, and Putative Carbon- and Nitrogen-Cycling Genes - Zarezadeh, Somayeh; Moheimani, Navid R.; Jenkins, Sasha N.; Hülsen, Tim; Riahi, Hossein; Mickan, Bede S. (Frontiers in Plant Science, 2019)
Microalgae (MA) and purple phototrophic bacteria (PPB) have the ability to remove and recover nutrients from digestate (anaerobic digestion effluent) and pre-settled pig manure that can be utilised as a bio-fertiliser. The objective of this study was to compare the effectiveness of MA and PPB as bio-fertilisers and soil conditioners in relation to plant growth and the soil biological processes involved in nitrogen (N) and carbon (C) cycling. To this end, a glasshouse experiment was conducted using MA and PPB as bio-fertilisers to grow a common pasture ryegrass (Lolium rigidum Gaudin) with two destructive harvests (45 and 60 days after emergence). To evaluate the rhizosphere bacterial community, we used barcoded PCR-amplified bacterial 16S rRNA genes for paired-end sequencing on the Illumina Mi-Seq. Additionally, we used phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt) analysis for the detection of putative functional genes associated with N and soil-C cycling. There was a significant increase in plant growth when the soil was amended with PPB, which almost performed as well as the chemical fertilisers. Analysis of the rhizosphere bacteria after the second harvest revealed a greater abundance of Firmicutes than in the first harvest. Members of this phylum have been identified as a biostimulant for plant growth. In contrast, the MA released nutrients more slowly and had a profound effect on N cycling by modulating N mineralisation and N-retention pathways. Thus, MA could be developed as a slow-release fertiliser with better N retention, which could improve crop performance and soil function, despite nutrient losses from leaching, runoff and atmospheric emissions. These data indicate that biologically recovered nutrients from waste resources can be effectively as a fertiliser, resulting in enhanced C- and N-cycling capacities in the rhizosphere.